Analisis Pertumbuhan Gulma, Tanaman dan Hasil Jagung dengan Berbagai Populasi Kacang Tanah dan Kacang Hijau dalam Sistem Tumpangsari - Hidayat Pujisiswanto; Kuswanta Futas Hidayat (Fakultas Pertanian, Universitas Syiah Kuala, 2008)
Weed-Crop Growth Analysis and Yield of Corn with Groundnut and Mungbean of Varying Plant Population in Intercropping SystemABSTRACT. The present experiment is designed to evaluated the weed-crop growth of intercrop between corn with mungbean and groundnut of varying plant populations. The experimental used the single factor field experiment that arranged with randomized completely block design with three block as replication. Intercropping followed additive series system, i.e.: (A) corn 100% + mungbean 25%, (B) corn 100% + mungbean 50%, (C) corn 100% + mungbean 75%, (D) corn 100% + groundnut 25%, corn 100% + groundnut 50%, (F) corn 100% + groundnut 75%. Experimental result showed that: Intercropping corn with groundnut and mungbean of able to weed growth suppressed of sedges, and Intercropping crop with groundnut at 75% rate of recommended population weed growth suppressed of total weeds compared to the other three mungbean populations. Intercropping corn with groundnut at 25% of recommended rate gave the highest sweet corn yield per hectare.